A companion to Woodrow Wilson - Kennedy, Ross A. (Chichester, West Sussex ; Malden, MA : Wiley-Blackwell, 2013)
"A Companion to Woodrow Wilson presents a compilation of essays contributed by various scholars in the field that cover all aspects of the life and career of America's 28th president. This book: Represents the only current anthology of essays to introduce readers to the scholarship on all aspects of Wilson's life and career ; Offers a 'one stop' destination for anyone interested in understanding how the scholarship on Wilson has evolved and where it stands now."--Publisher's website.
Introduction / Ross A. Kennedy. -- Part I: To the Presidency -- Wilson the Man / Mark Benbow -- Wilson's Religious, Historical, and Political Thought / Malcolm D. Magee -- Path to Power: Wilson as President of Princeton and Governor of New Jersey / Edmund D. Potter -- Presidential Politics and the Election of 1912 / William B. Murphy. -- Part II: National Progressivism and Wilson -- Wilson as Chief Executive: Relations with Congress, the Cabinet, and Staff / Robert C. Hilderbrand -- The New Freedom and its Evolution / W. Elliot Brownlee -- Wilson and Race Relations / Jennifer D. Keene -- Wilson's Views on Immigration and Ethnicity / Kristofer Allerfeldt -- The Election of 1916 / Nicole M. Phelps. -- Part III: Foreign Relations: Western Hemisphere and Asia, 1913-1921 -- Wilson and Mexico / Benjamin T. Harrison -- US Policies Toward Latin America / Michael E. Neagle -- US Policies Toward China, Japan, and the Philippines / Anne L. Foster -- Part IV: World War I: Neutrality to War -- Neutrality Policy and the Decision for War / Justus D. Doenecke -- Preparedness / Ross A. Kennedy. -- Part V: Wartime Progressivism, 1917-1921 -- Economic Mobilization / Mark R. Wilson -- Propaganda: Wilson and the Committee on Public Information / Richard L. Hughes -- Civil Liberties / Kathleen Kennedy -- Wilson and Woman Suffrage / Barbara J. Steinson. -- Part VI: Fighting World War I -- War Aims, 1917 to November 11, 1918 / John A. Thompson -- Policies Toward Russia and Intervention in the Russian Revolution / David S. Foglesong -- Wilson's Policies toward Eastern and Southeastern Europe, 1917-1919 / M.B.B. Biskupski -- Wilson and His Commanders / Jack McCallum. -- Part VII: Peacemaking: Paris and After -- Negotiating Peace Terms for Germany / Klaus Schwabe -- Wilson's Project for a New World Order of Permanent Peace and Security / William R. Keylor -- Wilson, Europe's Colonial Empires, and the Issue of Imperialism / Priscilla Roberts -- The League Fight / John Milton Cooper, Jr. -- Part VIII: Into the Twenties -- Red Scare / Adam J. Hodges -- The Election of 1920 / Allan J. Lichtman. -- Part IX: Wilson's Shadow -- Legacy and Reputation / Lloyd E. Ambrosius.
Includes bibliographical references and index.
Print version record.
Keywords: Wilson, Woodrow, -- 1856-1924.; Wilson, Woodrow, -- 1856-1924.; Presidents -- United States -- Biography; Presidents -- United States -- Biography; Presidents -- United States -- History; Wilson, Woodrow -- 1856-1924.; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; HISTORY -- United States -- 20th Century; Presidents; United States; Electronic books; Biography